2011
DOI: 10.2478/v10012-011-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cfd analysis to study the thrust and efficiency of a biologically-inspired marine propulsor

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Esta técnica é capaz de observar e entender os movimentos da água ao redor do corpo humano e sua aplicação para melhorar o desempenho na natação. O CFD é aplicado em muitas pesquisas (BANKS et al, 2014;RIEWALD, 2002;LAMAS et al, 2011;MANTHA et al, 2014;POPA et al, 2014) na tentativa de entender profundamente as bases biomecânicas da natação. Assim, esta técnica pode ser considerada uma nova abordagem relevante para avaliação das forças hidrodinâmicas na natação (GUIGNARD et al, 2017).…”
Section: Discussionunclassified
“…Esta técnica é capaz de observar e entender os movimentos da água ao redor do corpo humano e sua aplicação para melhorar o desempenho na natação. O CFD é aplicado em muitas pesquisas (BANKS et al, 2014;RIEWALD, 2002;LAMAS et al, 2011;MANTHA et al, 2014;POPA et al, 2014) na tentativa de entender profundamente as bases biomecânicas da natação. Assim, esta técnica pode ser considerada uma nova abordagem relevante para avaliação das forças hidrodinâmicas na natação (GUIGNARD et al, 2017).…”
Section: Discussionunclassified
“…Since the Fibonacci spiral is highly presented in nature, and thus is consequence of millions of years of evolution, it is appropriate to propose this geometry for VAWT wind turbines, obtaining a bio-inspired blade profile. In relation to this, some authors of the present work have proposed a bio-inspired shape for a marine propulsor elsewhere [32][33][34][35], improving the performance of the traditional propellers for certain applications. These works demonstrate that sometimes nature can appropriately inspire mechanical devices with surprising results.…”
Section: Blade Profilementioning
confidence: 99%
“…Another advantage is the possibility to swim backward, simply passing the undulation from tail to head. Due to its lower efficiency compared with other BCF modes, anguilliform swimming movement has only inspired a few robots that require high maneuverability, mimicking lampreys [32][33][34][35][36][37][38][39][40][41], snakes [42], salamanders [43][44][45], eels [46][47][48][49][50][51], etc.…”
Section: Bcf Swimming Modesmentioning
confidence: 99%
“…Lamas et al [49] developed an undulating propulsor actuated by several ribs. After that, Lamas et al [50,51] employed CFD (Computational Fluid Dynamics) to study several amplitudes, wavelengths, and oscillation frequencies in anguilliform, carangiform, thunniform, ostraciiform, and gymnotiform movements. They concluded that thunniform is the most efficient swimming mode in terms of the Froude efficiency, followed by caranguiform, ostraciiform, anguilliform, and finally, gymnotiform.…”
Section: Mpf Swimming Modesmentioning
confidence: 99%